Assuan, Ägypten Felsinschriften und Felsbilder der Region von Assuan - Borrmann, Linda (e-Forschungsberichte des DAI, 2023)
One of the specific features of the Aswan region and its landscape is an exceptionally high number of rock inscriptions and rock images. Among them, chronological and spatial groups can be distinguished. During the season 2014/2015 the project’s fieldwork focused on two of these groups of inscriptions: Tabyat al-Sheikh, the southernmost section of the ancient road leading from the bay of Shellal to Aswan/Elephantine, and the island of Sehel, a former cult centre of the local goddess Anuket. Even though the epigraphic sites seem to differ significantly in terms of their topography and their historical uses, on closer observation similarities can be discovered. In both cases, a group of Pharaonic rock images are thought to be linked to the protection and control of sensitive border areas within the First Cataract region.